Anti-scratch Properties of Clearcoat after Application of Polymer Coated Silica Ball - Noh, Seung Man; Choi, Ki Hyun; Ji, Soo Jeong; Hwang, Yun Kyoung; Kyu Park, Seung (Asian Journal of Chemistry, 2013)
Organic/inorganic hybrid materials such as core-shell hybrid nanocomposites have attracted great interest in automotive industry since they can be adjustable through the control of functionality of the components and exhibit markedly improved durability on outdoor weather and scratch. We have synthesized nano silica ball, g-methacryloxy propyl trimethoxy silane modified nano silica ball (NSB-g-MPS), nano silica ball core-polymethylmethacrylate shell hybrid complex (NSB-PMMA) and nano silica ball core-poly (MMA-AN- styrene) shell structured materials (NSB-MAS) and applied to conventional clearcoat and compared the anti-scratch properties by nano scratch tester.